Morphometric features of enterochromaffin endocrinocytes of the small intestine of piglets receiving prebiotic feed additive - N. V. Boniuk; O. I. Vishchur; Т. Y. Prudyus; O. M. Shchebentovska; H. I. Blishch (Regulatory Mechanisms in Biosystems, 2024)
Enterochromaffin endocrine cells play a key role in stimulating intestinal peristalsis and regulating metabolic disorders by releasing serotonin (5-HT) from their granules. They serve as intermediaries between the intestinal epithelium and specific primary afferent nerve fibers. Histologically, the specificity of enterochromaffin cell characteristics has been established, wherein they possess small secretory granules with pronounced diazo-reaction, located basally or around the nucleus. According to morphometric studies of the small intestine of piglets on day 7, the largest number of enterochromaffin endocrine cells was localized in the duodenum, averaging 7.8 cells per 0.45 mm² area, slightly fewer in the ileum at 5 cells, and the least number in the jejunum at 3.4 cells. On day 14 of the experiment, after feeding the piglets in the experimental group with the prebiotic feed additive “Globigen Jump Start”, there was a tendency for their number to increase by 5%, while on day 28, a significant increase of 26.5% was noted, indicating a positive effect on the release of serotonin and improved intestinal peristalsis. Tracking the dynamic change in the number of enterochromaffin cells in the jejunum of the experimental piglets from days 7 to 28 revealed a slight decrease on day 14 (5.9% reduction) and a trend towards an increase of 5.9% on day 28 compared to the value on day 7. Analysis of the quantitative indicators of enterochromaffin cells in the ileum of the control and experimental groups on day 14 also showed a significant difference, with an increase in the experimental group by 36.4% compared to control animals, maintaining this trend on day 28, where the number of enterochromaffin cells in the experimental group exceeded that in control animals by 16.9%. The volume of enterochromaffin cell’s nuclei in the duodenum of the experimental group on day 14 was 1% higher than that of the control group, while on day 28, the size of the nuclei tended to increase in both groups. A similar trend was observed in the jejunum; from days 7 to 28, the experimental piglets showed an increase in nuclear volume of 4.3% (day 14) and 6.5% (day 28) compared to the measurement on day 7. The volume of nuclei of enterochromaffin cells in the ileum of experimental piglets was 3.6% greater on day 14 and 3.0% on day 28 compared to the volume on day 7. Thus, the trend of increase in the volume of enterochromaffin endocrine cell nuclei, both on days 14 and 28 of the experiment in all segments of the intestinal tract of the experimental group may indicate active synthetic processes within the cell and stimulation of serotonin production with a positive impact on digestion and intestinal peristalsis.